Influência de gradientes espaciais sobre comunidades de macroinvertebrados aquáticos em áreas úmidas costeiras de dois biomas no sul do Brasil - Bacca, Roberta Cozer (Universidade do Vale do Rio dos Sinos, 2020)
Species do not have similar and uniform distributions along environmental gradients, due to biotic and abiotic restrictions. However, the effects of many environmental gradients on the structure of animal communities are still unknown. Aquatic macroinvertebrates are important representatives of wetland ecosystems, and their communities are influenced by the duration of the water and local, regional and spatial processes. In this sense, the general objective of the thesis was to analyze the beta diversity and evaluate the influence of spatial gradients on the taxonomic and functional structures of aquatic macroinvertebrate communities in coastal wetlands in southern Brazil in the Atlantic Forest and Pampa biomes. In relation to beta diversity, macroinvertebrate communities were studied in 24 lagoons on the coastal plain of the states in the states of SC and RS, distributed along a latitudinal gradient. We assessed the influence of local factors (water quality and habitat structure) and regional factors (climate) on the beta diversity of macroinvertebrate communities. Our study demonstrated that differences in species composition between wetlands are more strongly influenced by environmental differences than by geographic distance between wetlands. In terms of taxonomic and functional analysis of aquatic macroinvertebrates, communities were studied in 12 distributed ponds along a latitudinal gradient in the Coastal Plain of the states of SC and RS, between the Pampa and southern Atlantic Forest biomes, in two years (2015 and 2016). Regarding taxonomic analyzes, our study demonstrated that differences in species composition between wetlands are influenced by both local, regional and spatial environmental variables. For functional categorization, the genders were classified according to the characteristics of voltinism, dispersion, habits, trophic groups and maximum body size. The relative effects of the environment, climate and biome on the functional structure of the community were also evaluated. Our study demonstrated that the differences in the functional structuring of species between wetlands are influenced by both local, regional and spatial environmental variables. These results contribute to the ecology of wetlands and to a better understanding of the interactions between wetlands and aquatic macroinvertebrates.
Keywords: Banhados; Insetos aquáticos; Macroinvertebrados; Atributos funcionais; Diversidade beta; Wetlands; Aquatic insects; Macroinvertebrates; Functional attributes; Beta diversity; ACCNPQ::Ciências Biológicas::Biologia Geral